Search for the rare leptonic decay B--->tau-nutau. - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2005)
We present a search for the decay B(-)--> tau(-)nu(tau) in a sample of 88.9 x 10(6) BB pairs recorded with the BABAR detector at the Stanford Linear Accelerator Center B factory. One of the two B mesons from the Gamma(4S) is reconstructed in a hadronic or a semileptonic final state, and the decay products of the other B in the event are analyzed for consistency with a B(-) --> tau(-)nu(tau) decay. We find no evidence of a signal and set an upper limit on the branching fraction of B(B(-) --> tau(-) nu(tau)) < 4.2 x 10(-4) at the 90% confidence level.